Crystallization kinetics in AlxCrCoFeNi (0 ≤ x ≤ 40) high-entropy alloys. (December 2017) - Sharma, Aayush; Deshmukh, Sanket A.; Liaw, Peter K.; Balasubramanian, Ganesh
Abstract: We explore the atomic origins of the structural phase transformations (PTs) in Alx CrCoFeNi high entropy alloy (HEA) using classical molecular dynamics (MD) simulations. Our investigation critically reveals the role of Al content in triggering such diffusive transformations from a molten to a crystalline phase (for lower Al concentrations) or from molten to amorphous transitions (for Al fractions above the equiatomic alloy composition). Structural pair-correlation functions employed to provide atomistic evidence and mechanisms for the PTs show that the molten to amorphous PT initiates through the nucleation of a final child phase in the parent molten phase. Our structure predictions, although differ from earlier experimental observations, are confirmed by the predictions from common-neighbor analysis. Graphical abstract: